The effect of preoperative serum triglycerides and high-density lipoprotein-cholesterol levels on the prognosis of breast cancer. (April 2017) - Li, Xing; Tang, Hailin; Wang, Jin; Xie, Xinhua; Liu, Peng; Kong, Yanan; Ye, Feng; Shuang, Zeyu; Xie, Zeming; Xie, Xiaoming
Abstract: Objectives: Although dyslipidemia has been documented to be associated with several types of cancer including breast cancer, it remains uncertainty the prognostic value of serum lipid in breast cancer. The purpose of this study is to evaluate the association between the preoperative plasma lipid profile and the prognostic of breast cancer patients. Methods: The levels of preoperative serum lipid profile (including cholesterol [CHO], Triglycerides [TG], high-density lipoprotein-cholesterol [HDL-C], low-density lipoprotein-cholesterol [LDL-C], apolipoprotein A-I [ApoAI], and apolipoprotein B [ApoB]) and the clinical data were retrospectively collected and reviewed in 1044 breast cancer patients undergoing operation. Kaplan-Meier method and the Cox proportional hazards regression model were used in analyzing the overall survival [OS] and disease-free survival [DFS]. Results: Combining the receiver-operating characteristic and Kaplan-Meier analysis, w e found that preoperative lower TG and HDL-C level were risk factors of breast cancer patients. In multivariate analyses, a decreased HDL-C level showed significant association with worse OS (HR: 0.528; 95% CI: 0.302–0.923; P = 0.025), whereas a decreased TG level showed significant association with worse DFS (HR: 0.569; 95% CI: 0.370–0.873; P = 0.010). Conclusions: Preoperative serum levels of TG and HDL-C may be independent factor to predict outcome in breast cancer patient. Highlights: The cutoff value to stratify patients at high risk of death was established by receiver-operating curve analyses. Preoperative serum different levels of lipids may be independent prognostic factor in breast cancer patients. Surveillance and control the level of lipids may improve the prognosis of patients with breast cancer.